Polish Independent Press Summary, no. 37 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Solidarność Walcząca, no. 184 (7 August 1988). Extract from Solidarność Walcząca - Poznań, no. 96 (21 August 1988). Extract from Wiadomości Bieżące, no. 218 (23 July 1988). Extract from Głos Solidarności, no. 7 (June 1988). Extract from Z Dnia na Dzień, no. 469 (6 July 1988). Extract from Region, no. 15 (3 July 1988). Extract from Solidarność - Pismo Regionu Gdańskiego, no. 202 (16 July 1988).